The Impact of Good Corporate Governance and Profitability on Operational Risk Management at State Owned Banking Companies Listed on the IDX - Sumayyah Sumayyah; Muhammad Ilham Pakawaru; Abdul Kahar; Rika Febby Rhamadhani (DINASTI RESEARCH, 2026)
This research seeks to examine the effect of Good Corporate Governance (GCG) and profitability on operational risk in state-owned banking institutions registered on the Indonesia Stock Exchange during the period 2015–2024. The study employs a quantitative approach using purposive sampling. The data were processed through the SEM-PLS approach utilizing the assistance of WarpPLS 7.0. The results demonstrate that Good Corporate Governance possesses a negative and significant effect on operational risk. Additionally, profitability also has a negative and significant effect on operational risk. These findings suggest that as the application of governance mechanisms improves and profitability increases, operational risk proxied by the BOPO ratio tends to decrease. The research results imply that strengthening GCG practices and increasing profitability are important factors in supporting the effectiveness of operational risk control in state-owned banks.